2018
DOI: 10.1007/s12031-018-1078-2
|View full text |Cite
|
Sign up to set email alerts
|

GABAA Receptor Density Is Not Altered by a Novel Herbal Anxiolytic Treatment

Abstract: Anxiety disorders are highly prevalent and considered a major public health concern worldwide. Current anxiolytics are of limited efficacy and associated with various side effects. Our novel herbal treatment (NHT), composed of four constituents, was shown to reduce anxiety-like behavior while precluding a common side effect caused by current anxiolytics, i.e., sexual dysfunction. Nevertheless, NHT's mechanism of action is yet to be determined. There is evidence that some medicinal herbs interact with the GABAe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Recent in vivo and in vitro studies demonstrated a notable therapeutic potential of several herbal medications for depression and anxiety, with fewer adverse effects ( Burstein et al, 2017 ; Doron et al, 2018 , 2019 ; Russo et al, 2014 ; Sarris & Kavanagh, 2009 ; Yeung et al, 2014 ). Frequent use of such phytotherapies was observed among individuals with depression or anxiety ( Kessler et al, 2001 ; Pan et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent in vivo and in vitro studies demonstrated a notable therapeutic potential of several herbal medications for depression and anxiety, with fewer adverse effects ( Burstein et al, 2017 ; Doron et al, 2018 , 2019 ; Russo et al, 2014 ; Sarris & Kavanagh, 2009 ; Yeung et al, 2014 ). Frequent use of such phytotherapies was observed among individuals with depression or anxiety ( Kessler et al, 2001 ; Pan et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%